2014
DOI: 10.1007/s40315-014-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic Orbifolds of Minimal Volume

Abstract: We provide a survey of hyperbolic orbifolds of minimal volume, starting with the results of Siegel in two dimensions and with the contributions of Gehring, Martin and others in three dimensions. For higher dimensions, we summarise some of the most important results, due to Belolipetsky, Emery and Hild, by discussing related features such as hyperbolic Coxeter groups, arithmeticity and consequences of Prasad's volume, as well as canonical cusps, crystallography and packing densities. We also present some new re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Identifying the facets of a hyperbolic Coxeter polyhedron by using the reflections in their supporting hyperplanes is a simple way to construct hyperbolic n-orbifolds and n-manifolds. In the known cases, such polyhedra are responsible for minimal volume hyperbolic orbifolds and manifolds [10].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the facets of a hyperbolic Coxeter polyhedron by using the reflections in their supporting hyperplanes is a simple way to construct hyperbolic n-orbifolds and n-manifolds. In the known cases, such polyhedra are responsible for minimal volume hyperbolic orbifolds and manifolds [10].…”
Section: Introductionmentioning
confidence: 99%
“…Note that such a prime exists because we have already shown that there are infinitely many primes of k which are inert in all of the extensions L i /k. Before continuing we note that because the compact (respectively non-compact) hyperbolic 2-orbifold of minimal area has area π/42 (respectively, π/6), the fact that N(p 0 ) > 13 ensures that V 0 · (N(p 0 ) − 1) > 1 (see [6]). We will now construct our quaternion algebras B by choosing primes p of k which are unramified in B 0 and inert in all of the extensions L i /k, and then defining B to be the quaternion algebra for which Ram(B) = Ram(B 0 ) ∪ {p 0 , p}.…”
Section: A Useful Lemmamentioning
confidence: 99%
“…3, (3.1)) of the groups 2,3 and 2,4 is a discrete subgroup of Isom(H 3 ) containing both groups as subgroups of finite index. Observe that C is a non-cocompact but cofinite (nonarithmetic) group so that its covolume is universally bounded from below by the minimal covolume K(π/3)/8 in this class which is realised by the tetrahedral group [3,3,6] (see [25] and [19,Table 2]). This allows us to rewrite (4.4) according to Table 2 Commensurability classes N n in the non-arithmetic case…”
Section: P N−1 Q ∞] Then Is a Subgroup Of Index 2 In θmentioning
confidence: 99%